Literature Review: Peran Perilaku Seks Anal Berisiko pada Laki Seks dengan Laki (LSL) terhadap Transmisi HIV - Ni Putu Diwyami; A.A Bagus Suryantara (Jurnal Kesehatan Medika Udayana, 2021)
Background: This study is a literature study that employed descriptive qualitative research design with a library research approach to describe the risk of unsafe anal sex roles behavior among men who have sex with men (MSM) towards HIV transmission. In this literature study, the researcher used various written resources to obtain the data such as journal articles that were relevant to the present study. Purpose: This study focused on measuring the prevalence of risky anal sex roles among MSM and the risk of those roles towards HIV transmission. Result: The results of this study showed that the unsafe anal sex behavior among MSM towards HIV transmission was highly founded in the receptive role compared to the insertive role or versatile role. Conclusion: MSM who performed the receptive role during the unsafe anal sex were more exhibited by young MSM. In order to decrease the risk of sexual behavior among MSM, it is necessary to start it over young MSM. Therefore, the increasing incidence of HIV among MSM can be controlled as well.